Common Ground (Volume 10) - de Grey, Spencer (European Investment Bank, 2019)
By 2050, three-quarters of the world's 9.6-billion-strong population will be living in cities - inhabiting vibrant historic cores, commuting from new hinterlands via high-speed transit, or occupying informal urban settlements. Some cities will flourish while others will struggle to meet the demands of a growing population and a changing environment. It will take the collaborative expertise of various disciplines, gathered under the umbrella of good governance, to ensure our cities thrive in the future. Spencer de Grey, Head of Design at Foster + Partners, explores the role that architecture and urban design can play in this global endeavour. This is the tenth essay in the Big Ideas series created by the European Investment Bank. The EIB has invited international thought leaders to write about the most important issues of the day. These essays are a reminder that we need new thinking to protect the environment, promote equality and improve people's lives around the globe.